2014
DOI: 10.1038/pr.2014.168
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and bio-activation of nitrite and nitrate in newborn infants

Abstract: Nitrate and nitrite are commonly thought of as inert end products of nitric oxide (NO) oxidation, possibly carcinogenic food additives, or well-water contaminants. However, recent studies have shown that nitrate and nitrite play an important role in cardiovascular and gastrointestinal homeostasis through conversion back into NO via a physiological system involving enterosalivary recirculation, bacterial nitrate reductases, and enzyme-catalyzed or acidic reduction of nitrite to NO. The diet is a key source of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 88 publications
(122 reference statements)
0
25
0
Order By: Relevance
“…Notwithstanding the likely cardiovascular benefits of nitrate from dietary vegetables, high levels of dietary nitrate or nitrite can be problematic for very young infants. In the newborn, both serum nitrate and nitrite are at very low concentrations for the first few weeks of their lives . It is well established that excessive gastrointestinal nitrite absorption puts young infants at risk of methemoglobinemia (met‐Hb) because of a neonate's high proportion of fetal hemoglobin and relative lack of metHb‐reducing capacity .…”
Section: Nitrite and Infant Methemoglobinemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the likely cardiovascular benefits of nitrate from dietary vegetables, high levels of dietary nitrate or nitrite can be problematic for very young infants. In the newborn, both serum nitrate and nitrite are at very low concentrations for the first few weeks of their lives . It is well established that excessive gastrointestinal nitrite absorption puts young infants at risk of methemoglobinemia (met‐Hb) because of a neonate's high proportion of fetal hemoglobin and relative lack of metHb‐reducing capacity .…”
Section: Nitrite and Infant Methemoglobinemiamentioning
confidence: 99%
“…It is well established that excessive gastrointestinal nitrite absorption puts young infants at risk of methemoglobinemia (met‐Hb) because of a neonate's high proportion of fetal hemoglobin and relative lack of metHb‐reducing capacity . Very young infants, with their undeveloped oral microbiome, do not produce nitrite from salivary nitrate . But preformed nitrite from improperly stored vegetable purees fed to young infants, or nitrite formed in their stomach from overgrowth of nitrate‐reducing bacteria, can cause MetHb.…”
Section: Nitrite and Infant Methemoglobinemiamentioning
confidence: 99%
“…, and NO 2 − reacts with hemoglobin and prevents oxygen transport to the tissues. As a result, "methemoglobinemia" known as "blue baby syndrome" occurs in infants [47].…”
Section: Nomentioning
confidence: 99%
“…We have previously demonstrated that newborn infants have lower blood nitrite concentrations than adults, possibly due to markedly lower levels of nitrate and nitrite ingestion (12). Preterm infants in particular ingest 50% less nitrite than term infants (12), leading us to hypothesize that nitrate and nitrite levels would be decreased in preterm compared to term infants.…”
mentioning
confidence: 99%
“…Preterm infants in particular ingest 50% less nitrite than term infants (12), leading us to hypothesize that nitrate and nitrite levels would be decreased in preterm compared to term infants. Furthermore, given animal evidence for the protective effects of nitrite in the gastrointestinal tract, we hypothesized infants diagnosed with NEC would have lower levels of circulating nitrite in the days prior to diagnosis.…”
mentioning
confidence: 99%